Technical Universities Past, present and future - Geschwind, Lars; Broström, Anders; Larsen, Katarina (Higher Education Dynamics, 2020)
This Open Access book analyses the past, present and future of the technical university as a single faculty independent institution. The point of departure is a view of changing academic realities, through which the identity as a technical university is challenged and reconstituted. More specifically, the book connects the development of technical universities to changes in the structure and dimensioning of national higher education systems, to changes in the disciplinary basis of academic research and to changes in the governance of higher education institutions. Introduced in the age of industrialization, polytechnical schools rose to prominence in many national settings during the second half of the 19th century. Over time, new technologies have been developed and incorporated into the repertoire, and waves of academisation have swept over the former polytechnics, transforming them into technical universities. Their traditions and brands, however, prevail. Several technical universities are included among the most prestigious academic institutions of their nations and the training of engineers and engineering research still enjoys a high level of prestige and national priority, e.g. in the context of innovation and industrial policy. But the world keeps changing, and the higher education sector with it. Will technical universities have an equally attractive position within university systems in the decades to come?